2018
DOI: 10.3390/nu10060665
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Cholesterol Intake Is Not Associated with Risk of Type 2 Diabetes in the Framingham Offspring Study

Abstract: Identification of diet and lifestyle risk factors for prevention of type 2 diabetes mellitus (T2DM) is of great importance. The specific role of dietary cholesterol (DC) in T2DM risk is unclear. This study uses data from 2192 Framingham Offspring Study subjects to estimate the effects of DC alone and in combination with markers of a healthy diet and other lifestyle factors on fasting glucose and risk of T2DM or impaired fasting glucose (IFG) over 20 years of follow-up. Dietary data were derived from two sets o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 34 publications
0
6
0
2
Order By: Relevance
“…440 Resultados baseados na população do Framingham Offspring Study, seguida por 20 anos, demonstraram falta de associação entre o consumo de colesterol alimentar e perfil lipídico em jejum e também no risco de DCV de indivíduos portadores de glicemia de jejum alterada ou DM2. 441 Análise do estudo prospectivo da população do estudo PREDIMED, que incluiu participantes sem eventos cardiovasculares prévios e acompanhados em média por 5,8 anos, concluiu que o consumo baixo ou moderado de ovos não aumentou o risco de DCV tanto nos indivíduos portadores quanto nos não portadores de DM2. 442 Resultados de estudos prospectivos randomizados e observacionais, assim como as revisões sistemáticas e metanálises, são inconclusivos para a associação entre o maior consumo alimentar de colesterol e maior risco de DCV nos casos de DM2, em virtude da grande heterogeneidade das populações avaliadas e metodologias aplicadas.…”
Section: Risco De Doenças Cardiovasculares Em Diabetes Melito Tipounclassified
“…440 Resultados baseados na população do Framingham Offspring Study, seguida por 20 anos, demonstraram falta de associação entre o consumo de colesterol alimentar e perfil lipídico em jejum e também no risco de DCV de indivíduos portadores de glicemia de jejum alterada ou DM2. 441 Análise do estudo prospectivo da população do estudo PREDIMED, que incluiu participantes sem eventos cardiovasculares prévios e acompanhados em média por 5,8 anos, concluiu que o consumo baixo ou moderado de ovos não aumentou o risco de DCV tanto nos indivíduos portadores quanto nos não portadores de DM2. 442 Resultados de estudos prospectivos randomizados e observacionais, assim como as revisões sistemáticas e metanálises, são inconclusivos para a associação entre o maior consumo alimentar de colesterol e maior risco de DCV nos casos de DM2, em virtude da grande heterogeneidade das populações avaliadas e metodologias aplicadas.…”
Section: Risco De Doenças Cardiovasculares Em Diabetes Melito Tipounclassified
“…Interestingly, stratification by dietary sources revealed that fatty acids originating from meat were positively associated with insulin resistance and secretion, but no such association was observed in case of fatty acids originating from dairy and plant sources, providing a conclusion that association between fatty acids and risk of T2DM may be dependent on dietary sources [46]. Results from Framingham Offspring Study indicated, that although total dietary cholesterol was not associated with increased risk of T2DM or impaired fasting glucose, in contrast, higher intake of fish, whole-grain products and fiber were associated with lower risk of T2DM [44]. Red and processed meat are also a source of heme iron, heterocyclic amines (HCAs) and nitrates, the excess of which can play role in deterioration of glucose metabolism [47], though in case of HCAa and nitrates, the evidence come mostly from animal studies [48,49].…”
Section: Meat Fish Eggsmentioning
confidence: 95%
“…Meat is a source of SFA and dietary cholesterol, but neither total dietary SFA [43], nor dietary cholesterol [44] have been associated with increased risk of T2DM in recent studies. Those conclusions were contrary to results obtained in the study by Guess et al [45] in which researchers compared the intake of fatty acids between normoglycaemic participants, prediabetes participants and participants with type 2 diabetes, and provided observation that increased consumption of saturated fatty acids was associated not only with higher risk of impaired fasting glucose and higher concentration of glucose after 2h in OGTT (Oral Glucose Tolerance Test), but also with insulin resistance.…”
Section: Meat Fish Eggsmentioning
confidence: 99%
“…Inadequate dietary AAs compositions therefore may play important roles in the development of T2DM. This study also demonstrated that when additionally adjusted for other known dietary risk factors for T2DM including intake of total protein [ 16 ], lipid [ 17 ], cholesterol [ 18 ], carbohydrate [ 19 ], fiber [ 20 ], saturated fat [ 21 ], fatty acids [ 22 ], and overall diet quality [ 23 ], the relationship between the AACI and incidence of T2DM was still significant, further indicating that inadequate dietary AAs composition was likely an important dietary factor for residual risk of T2DM. These findings are supported by previous studies, a population-based study showed that the risk of pre-diabetes varied with different dietary AAs patterns, which play an important role in glucose metabolism [ 24 ].…”
Section: Discussionmentioning
confidence: 78%